How Do Regular Students in Inclusive Primary Schools Interpret the Term of 'Students with Special Needs'? - Wardany, Ossy Firstanti (The Center for Disability Studies and Services Brawijaya University, 2020)
A positive perception toward the student with special needs required to build positive attitudes and behaviours in inclusive schools. The aim of this study is to determine the perception of regular students in inclusive primary schools toward students with special needs. This study is a survey and the participants are 146 regular students in inclusive primary school. The study used questionnaires. The results show that only 35% of regular students who know and can interpret the definition of the student with special needs into the text. Most students interpret based on what they see, such as a physical problem, low academic achievement or help by shadow teacher. There are still misconceptions, stereotypes, and negative perception toward students with special needs. It suggests for the teachers in inclusive school for increase disability awareness to overcome the negative perception.